Repair of vascular accesses for hemodialysis - López Chapuis, Daniel; Elters, Antoine; Garrido, Pedro; Prego, Alfredo; Valverdu, Martín (Cirugía del Uruguay, 1993)
The author analyses the experience in repair of angioaccesses far hemodialysis, mostly studied by means of fistulography. Among the 27 procedures, those designed far treatment of arteriovenous stenosis (N=14) ar venous exit stenosis (N=9) predomina/e. In 25 cases repair was successful, making possible the continuation of hemodyalisis through that access frequently.